Oxford Research Encyclopedia of Economics and Finance 2019
DOI: 10.1093/acrefore/9780190625979.013.464
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Gender Differences in Negotiation

Abstract: Gender differences, both in entering negotiations and when negotiating, have been proved to exist: Men are usually more likely to enter into negotiation than women and when negotiating they obtain better deals than women. These gender differences help to explain the gender gap in wages, as starting salaries and wage increases or promotions throughout an individual’s career are often the result of bilateral negotiations. This article presents an overview of the literature on gender differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Negotiations are among the most consequential of social interactions because their results impact individuals’ lives, careers, families and financial outcomes substantially. Past research has revealed some gender differences in negotiation intentions and behaviors that put women at a disadvantage (Bowles et al , 2007; Greig, 2008; Hernandez-Arenaz and Iriberri, 2019; Pfeifer and Stephan, 2019; Small et al , 2007; Walters et al , 1998). However, findings comparing the two genders’ economic outcomes have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Negotiations are among the most consequential of social interactions because their results impact individuals’ lives, careers, families and financial outcomes substantially. Past research has revealed some gender differences in negotiation intentions and behaviors that put women at a disadvantage (Bowles et al , 2007; Greig, 2008; Hernandez-Arenaz and Iriberri, 2019; Pfeifer and Stephan, 2019; Small et al , 2007; Walters et al , 1998). However, findings comparing the two genders’ economic outcomes have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, employees passively rely on their managers’ negotiation styles for fair outcomes (Lind and van den Bos, 2002). Resultantly, they tend to be more contriently interdependent (Hernandez-Arenaz and Iriberri, 2019), and hence, they distrust the manager and be asocial in self-presentation during the performance review (Comeau and Griffith, 2005). Similarly, employees who foresee an unfair performance review outcome because of the manager’s negotiation style might experience dejection, perceive their behavioral options decreasing, opt out of selecting future situations and quit the organization (Erdogan, 2002; Ikramullah et al , 2016).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Overall, women are less likely to initiate and participate in negotiations compared to men (Babcock et al 2006;Gerhart and Rynes 1991;Hernandez-Arenaz and Iriberri 2019;Kugler et al 2018;O'Shea and Bush 2002), and individual differences in the type of negotiation strategies used also account for who is likely to initiate and receive benefit from the negotiation attempt (Marks and Harold 2009). Social role theory explains that beliefs about assumed gender roles guide the perceptions of men's and women's social roles within society (Eagly and Wood 2012), which contributes to the assignment of gender-specific attitudes in negotiation situations.…”
Section: Early Work Experiencesmentioning
confidence: 99%